Quantitative assessment of urban surface deformation risks from tectonic and seismic activities using multitemporal microwave satellite remote sensing: a case study of Almaty city and its surroundings in Kazakhstan - Bayramov, Emil; Sydyk, Nurmakhambet; Nurakynov, Serik; Yelisseyeva, Alena; Neafie, Jessica; Aliyeva, Saida (Frontiers in Built Environment, 2024)
The research goal of these studies was to monitor ground deformations for Almaty city during 2017–2023 and determine the spatial relationships with faults and tectonic plate boundaries. The small baseline subset interferometric synthetic aperture radar (SBAS-InSAR) was deployed for the interferometric measurements of ground deformations using Sentinel-1 radar satellite images. Distinct deformation patterns were observed from both sides of the tectonic plate boundary, indicating a standard faulting process. Identical deformation trends were observed from south to north, forming three transition zones from subsidence to uplift and subsidence again. The spatial relationship between faults and ground deformations was also observed in the transition zone with a densely built-up area subject to gradual surface declination with potential risks to infrastructure. Five incidents of building and bridge deformations with subsiding cumulative trends were observed in the same location. Most subsiding areas were in Zone 1, with maximum annual subsidence velocity and cumulative displacement of − 57 mm/y and – 399, respectively. In contrast, most uplifting areas were primarily in Zone 2, with maximum yearly uplift velocity and cumulative displacement of 40 mm/y and 254 mm, respectively, and mixed deformation patterns in Zone 3. These vertical movements in Almaty verify active tectonic plate activity that should be integrated into city risk assessment plans.